Environmental margin and island evolution in Middle Eastern populations of the Egyptian fruit bat - Hulva, P; Marešová, T; Dundarova, H; Bilgin, R; Benda, P; Bartonička, T; Horáček, I (Molecular ecology, 2012)
Here, we present a study of the population genetic architecture and microevolution of the Egyptian fruit bat (Rousettus aegyptiacus) at the environmental margins in the Middle East using mitochondrial sequences and nuclear microsatellites. In contrast to the rather homogenous population structure typical of cave-dwelling bats in climax tropical ecosystems, a relatively pronounced isolation by distance and population diversification was observed. The evolution of this pattern could be ascribed to the complicated demographic history at higher latitudes related to the range margin fragmentation and complex geomorphology of the studied area. Lineages from East Africa and Arabia show divergent positions. Within the northwestern unit, the most marked pattern of the microsatellite data set is connected with insularity, as demonstrated by the separate status of populations from Saharan oases and Cyprus. These demes also exhibit a reduction in genetic variability, which is presumably connected with founder effects, drift and other potential factors related to island evolution as site-specific selection. Genetic clustering indicates a semipermeability of the desert barriers in the Sahara and Arabian Peninsula and a corridor role of the Nile Valley. The results emphasize the role of the island environment in restricting the gene flow in megabats, which is also corroborated by biogeographic patterns within the family, and suggests the possibility of nascent island speciation on Cyprus. Demographic analyses suggest that the colonization of the region was connected to the spread of agricultural plants; therefore, the peripatric processes described above might be because of or strengthened by anthropogenic changes in the environment.
Keywords: tok genů; Animals; Genotype; Gene Flow; Africa, Eastern; Middle East; DNA, Mitochondrial; Chiroptera; Bayesova věta; shluková analýza; Střední východ; Molecular Sequence Data; genotyp; Bayes Theorem; Evolution, Molecular; molekulární evoluce; ostrovy; Genetic Variation; Genetics, Population; molekulární sekvence - údaje; Islands; mitochondriální DNA; Microsatellite Repeats; Sequence Analysis, DNA; zvířata; sekvenční analýza DNA; Cluster Analysis; východní Afrika; genetická variace; mikrosatelitní repetice; populační genetika